Prevalence Of Job Strain And Risk Factors For Job-Related Depression In Laboratory Technicians In Hospital Unversiti Sains Malaysia (HUSM) And Kementerian Kesihatan Malaysia (KKM) Hospitals In Kelantan. - Aziah, B.D.; Rusli, B.N.; T Winn, Dr PH; Naing, L (2003)
A cross-sectional study was conducted to determine the prevalence of job strain and association between high job strain and other risk factors with job-related depression in laboratory technicians in Hospital Universiti Sains Malaysia (HUSM) and Kementerian Kesihatan Malaysia (KKM) Hospitals in Kelantan between June 2001 and February 2002.